Sinosenecio qii (Asteraceae, Senecioneae), a hitherto imperfectly known species from southern Hunan, China - Fei, Wen-Qun; Zeng, You-Pai; Yang, Qin-Er (Phytotaxa, 2023)
Sinosenecio qii (Asteraceae, Senecioneae) was described on the basis of a fruiting plant from Jianghua county in southern Hunan province, China. This species has been imperfectly known because of the scantiness of material. Based on the results of our careful observations of the morphological characters of living plants within a population of this species at its type locality and the examination of its chromosome number, here we determine that S. qii is related to S. globiger in having epappose and glabrous achenes, polar and radial anther endothecial cell wall thickenings and a chromosome number of 2n = 48, but it is distinctive in having scapiform (vs. leafy) stems with only radical (vs. radical and cauline) leaves subentire (vs. shallowly 3–5-lobed), and fewer ray florets (8 vs. 13). The morphological description of S. qii is amended.